Neonatal bilirubin production-conjugation imbalance: effect of glucose-6-phosphate dehydrogenase deficiency and borderline prematurity. Issue 2 (21st February 2005) - Kaplan, M; Muraca, M; Vreman, H J; Hammerman, C; Vilei, M T; Rubaltelli, F F; Stevenson, D K
Abstract : Objective: To evaluate relations between production and conjugation of bilirubin in the pathophysiology of jaundice in glucose-6-phosophate dehydrogenase (G6PD) deficient neonates. Methods: Term and borderline premature (35–37 weeks gestational age), healthy, male, G6PD deficient neonates were studied close to the beginning of the 3rd day. Blood carboxyhaemogobin corrected for inspired CO (COHbc; an index of bilirubin production) and serum total conjugated bilirubin (TCB; a reflection of bilirubin conjugation) were measured in simultaneously drawn blood samples by gas chromatography and reverse phase high performance liquid chromatography respectively. A bilirubin production-conjugation index comprising COHbc/TCB was determined; a high index reflects imbalance between the bilirubin production and conjugation processes. COHbc and TCB individually and the production-conjugation index were studied in relation to serum total bilirubin (STB) concentration. Results: Fifty one G6PD deficient neonates were sampled at 51 (8) hours. COHbc values did not correlate with STB ( r = 0.22, p = 0.15). TCB did correlate inversely with STB ( r = −0.42, p = 0.004), and there was a positive correlation between the production-conjugation index and STB ( r = 0.45, p = 0.002). The production-conjugation index (median (interquartile range)) was higher in the premature (n = 8) than term neonates (2.31 (2.12–3.08) v 1.05 (0.53–1.81), p = 0.003). This difference was the result of changes in TCB. Conclusions: The data show that jaundice in G6PD deficient neonates is the result of an imbalance between production and conjugation of bilirubin with a tendency for inefficient bilirubin conjugation over increased haemolysis in its pathogenesis. Borderline premature infants are at especial risk of bilirubin production-conjugation imbalance.